Association Between Obesity and Vitamin D - Faid, Fathia; Eljamay, Salwa Muftah (Indonesian Journal of Community Services, 2024)
This study aimed to assess the demographic profile of participants in terms of weight, height, body mass index (BMI), waist circumference (WC), and nutritional status by BMI and WC. Study design/methodology/approach: The study involved collecting data from a sample of participants regarding their weight, height, BMI, WC, and nutritional status. Mean and standard deviation (SD) values were calculated for each variable. Findings: The mean weight of the participants was 78.1 kg (SD = 13.8), with a mean height of 158.4 cm (SD = 4.6). The average BMI was 31.2 kg/m2 (SD = 5.7), while the mean WC was 94.5 cm (SD = 16.8). In terms of nutritional status by BMI, 0.6% of participants were classified as underweight, 15.8% fell within the normal range, 23.1% were overweight, and 60.4% were obese. Among the obese participants, 59.2% were classified as obese class 1, 33.5% as obese class 2, and 7.3% as obese class 3. Regarding obesity co-morbidity risk by WC, 62 participants had a normal WC, 58 were at risk level 1 (WC > 80cm), and 196 were at risk level 2 (WC > 88cm). Originality/value: This study provides valuable insights into the demographic profile of participants, including weight, height, BMI, WC, and nutritional status. The findings highlight the prevalence of obesity and its associated co-morbidity risk, which can contribute to the development of targeted interventions and prevention strategies.